2014
DOI: 10.1016/j.celrep.2014.03.025
|View full text |Cite
|
Sign up to set email alerts
|

Folliculin Controls Lung Alveolar Enlargement and Epithelial Cell Survival through E-Cadherin, LKB1, and AMPK

Abstract: Summary Spontaneous pneumothoraces due to lung cyst rupture afflict patients with the rare disease Birt-Hogg-Dubé (BHD) syndrome caused by mutations of the tumor suppressor gene folliculin (FLCN) by unknown mechanism. BHD lungs exhibit increased alveolar epithelial cell apoptosis. We show that Flcn deletion in lung epithelium leads to cell apoptosis, alveolar enlargement and impaired lung function. FLCN loss also impairs alveolar epithelial barrier function. Flcn-null epithelial cell apoptosis is the result of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
90
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(101 citation statements)
references
References 49 publications
10
90
0
1
Order By: Relevance
“…85,86 Increased cell-cell adhesions were reported in FLCN -deficient lung cell lines in vitro 87 and marked reduction in E-cadherin expression at adherens junctions and increased alveolar apoptosis were observed in lungs of mice with lung-targeted Flcn inactivation. 88 These findings support a role for FLCN in maintaining critical cell-cell adhesions for maintenance of lung and kidney epithelial cell integrity ( Figure 7 ).…”
Section: Potential Pathways In Bhd Tumorigenesissupporting
confidence: 71%
“…85,86 Increased cell-cell adhesions were reported in FLCN -deficient lung cell lines in vitro 87 and marked reduction in E-cadherin expression at adherens junctions and increased alveolar apoptosis were observed in lungs of mice with lung-targeted Flcn inactivation. 88 These findings support a role for FLCN in maintaining critical cell-cell adhesions for maintenance of lung and kidney epithelial cell integrity ( Figure 7 ).…”
Section: Potential Pathways In Bhd Tumorigenesissupporting
confidence: 71%
“…It results from mutations of the Folliculin ( FLCN ) gene, a tumor suppressor gene (53, 54). The exact mechanism of pulmonary cyst formation is unclear, but may involve alterations in the mTOR pathway (55), altered cell-cell adhesion resulting in increased vulnerability to mechanical forces (56), impaired LKB1-AMPK signaling (57) and disordered extracellular matrix remodeling involving MMP’s (58). …”
Section: Introductionmentioning
confidence: 99%
“…Loss of FLCN induced alveolar epithelial dysfunction. In FLCN-null mice, impairment of AMPK activation increases the level of cleaved caspase-3, which leads to alveolar epithelial apoptosis35. Another study showed that AMPK activator AICAR induces apoptotic cell death and diminishes adiposity in adipocytes36.…”
Section: Discussionmentioning
confidence: 99%